Digitalization of management control in hospitals: an interventionist case study - Stefano Baraldi; Andrea Mariani; Federico Umberto Mion (Journal of Health Organization and Management, 2026)
Purpose This article aims to contribute to the debate on the digitalization of management control and the evolving role of controllers in healthcare organizations. Specifically, it uncovers recurring patterns through which digitalization progressively reshapes control activities and indirectly transforms the controller's role. Design/methodology/approach Drawing on literature on digitalization in management accounting and performance measurement in healthcare, the study presents longitudinal empirical evidence from an interventionist case study of a Swiss public hospital. Findings Despite the growing interest in digital technologies, digitalization unfolded through a limited set of interconnected use cases rather than widespread technology adoption. The evidence shows that the digitalization of management control follows multiple, coexisting patterns that progressively reshape control activities, shift control from retrospective evaluation toward more real-time and forward-looking orientations, and, over time, indirectly transform the controller's role. These transformations carry direct implications for how healthcare organizations govern performance across clinical, operational, and financial domains. Research limitations/implications The findings derive from a single interventionist case in a Swiss public hospital, which limits statistical generalizability. The interventionist design also introduces risks of prospective bias and narrative selectivity in participants' accounts. Practical implications This research offers a framework to understand how digitalization reshapes management control through changes in control activities and practices and highlights the need for organizations to develop integrated technical, analytical, and relational competencies for controllers in digitally transforming environments. Originality/value The study advances the literature by identifying a patterned and processual explanation of how digitalization reshapes management control activities over time and how role transformation emerges as an indirect outcome of these changes.